Water Defluoridation by Lignite - Kohli, S. K..; Chaudhuri, M. (Technoscience Publications, 2007)
Lignite (raw or alum-treated) was found to possess about one-half the fluoride sorption capacity of commercial grade activated alumina. No significant difference in performance of raw and alum-treated lignite in five cycles of defluoridation column test at pH 5.0 ± 0.2, using hydrochloric acid as regenerant, was observed. Infrared spectra indicated interaction of fluoride with carbonyl and aromatic ring functional groups in lignite. The results call for long-duration column tests, employing fluoride-bearing groundwater of varied characteristics and at natural pH, to confirm suitability of lignite as a low-cost medium for home water defluoridation in rural areas of developing countries.